DETERMINASI ENERGI POTENSIAL AIR TANAH ULTISOL LIMAU MANIS DENGAN METODA KOLOM AIR, KERTAS SARING, DAN TEKANAN UDARA - Asmar Asmar; Yulnafatmawita Yulnafatmawita; Ari Ramayani (Jurnal Solum, 2006)
Water content at several levels of soil water potential is important to determine soil water available for plant growth.  Standard method used to analyse soil water potential is by using Pressure and membrane Plate Apparatus.  Alternative methods can be used are by using Buchner Tunnel and Filter paper Methods.  This research was aimed to compare the results of Buchner Tunnel and Filter paper Methods on Pressure method in determining soil water potential.  The result showed that, from the two alternative methods tested, KA tanah determined by filter paper method gave results closer to the pressure method for Ultisol Limau Manis.  Then, among three laboratoriums giving services on soil water potential determination by using Pressure plate apparatus, laboratorium of soil physics from Jambi University gave results which were more rational to the soil physical properties of Ultisol Limau Manis.Key Words: Soil water potential, plant available water, Buchner tunnel, filter paper, pressure plate apparatus